ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN STUDI KASUS CAPELLA HONDA 88 DAN AHASS PANGERAN MOTOR - Elverina, Wenni; Kartikowati, Sri; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : the purpose of the research was to identity the influenc of service quality to the costumer satisfaction by company of compare two motorcyle service stations. The two stations are: Capella Honda 88 and AHASS Pangeran Motor with sixty sampel of thirty in Capella Honda 88 and thirty in AHASS Pangeran Motor make use of isidental sampling method. Data was collected through questionnaire to costumer consisted of 30 costumers for Capella Honda 88 and 30 costumers for AHASS Pangeran Motor. Data was analyzed by using multiple Linear Reggresion Analysis dan Independent Samples Test processed trough SPSS 20.0 program. The result of this reseach refer to that in Capella Honda 88 service quality influence on the costumer satisfaction and at AHASS Pangeran Motor service quality not influence on the costumer satifaction. The result Independent Samples Test srvice quality in Capella Honda 88 and AHASS Pangeran Motor not difference service quality gived to costumer satifaction.Keyword: Service Quality, Costumer Satifaction